2011
DOI: 10.1038/onc.2011.409
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactive EGF receptor, Jaks and Stat3 signaling promote enhanced colony-forming ability, motility and migration of cisplatin-resistant ovarian cancer cells

Abstract: We present evidence that the cisplatin-resistant human ovarian cancer lines, A2780S/CP1 (S/CP1), A2780S/CP3 (S/CP3), and A2780S/CP5 (S/CP5), derived by subjecting the sensitive A2780S ovarian cancer line to multiple rounds of cisplatin treatments followed by recovery and are resistant to 1, 3, and 5 μM cisplatin, respectively, have increased colony-forming ability and altered morphology that is consistent with enhanced motility, migration, and invasiveness in vitro. The malignant phenotype progresses with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 48 publications
4
114
3
Order By: Relevance
“…This directed cell migration is often regulated by responses to extracellular stimuli (33)(34)(35). Notably, signal transduction via EGFR has an important role in cell motility in various types of cancer (36,37). In the present study, EGF-EGFR signaling was identified to be required for the migration of SAS OSCC cells, but not for HSC4 OSCC cells.…”
Section: Discussionmentioning
confidence: 56%
“…This directed cell migration is often regulated by responses to extracellular stimuli (33)(34)(35). Notably, signal transduction via EGFR has an important role in cell motility in various types of cancer (36,37). In the present study, EGF-EGFR signaling was identified to be required for the migration of SAS OSCC cells, but not for HSC4 OSCC cells.…”
Section: Discussionmentioning
confidence: 56%
“…Additionally, expression of EGFR is altered in a variety of human cancer types, including carcinoma of the lung, breast, head and neck, ovary and bladder, as well as in glioma (35)(36)(37). STAT3 and EGFR serve notable roles in tumor development and metastasis (34,38). The results of the present study indicated that GEA significantly inhibited tumor metastasis by reducing levels of p-STAT3 and p-EGFR.…”
Section: Levels Of Phosphorylated Stat3 (P-stat3) and P-vegf In Lung supporting
confidence: 51%
“…3). The levels of p-STAT3 and p-EGFR in group G were slightly lower than those in group C. It was shown that there were significantly (P<0.05) lower levels of p-STAT3 and p-EGFR in group G + E than in groups C and G. Evidence indicates that aberrant STAT3 signaling promotes the initiation and progression of human cancer by either inhibiting apoptosis or inducing cell proliferation, angiogenesis, invasion and metastasis (32)(33)(34). Additionally, expression of EGFR is altered in a variety of human cancer types, including carcinoma of the lung, breast, head and neck, ovary and bladder, as well as in glioma (35)(36)(37).…”
Section: Levels Of Phosphorylated Stat3 (P-stat3) and P-vegf In Lung mentioning
confidence: 94%
“…[119][120][121] EMT is an important part of ovarian cancer progression, in which free floating spheroids attach to the mesothelium, disseminate and metastasize to surrounding tissues. 122,123 Expression of CD44 and CA125, high levels of IL-6, CXR4, and CXCL12 and the amplification of PIK3CA, Akt and bone morphogenetic protein (BMP) pathways have been associated with ovarian cancer EMT. 17,124,125 The review by Tan et al provides an in-depth look at epithelial ovarian cancer metastasis.…”
Section: Relating In Vitro Mechanotransduction Results To In Vivmentioning
confidence: 99%